Awareness and involvement of local communities adjacent Kihansi catchment in conservation of the re-introduced Kihansi spray toads (Nectophrynoides asperginis) - Atuhombye Sigala; Kelvin Ngongolo; Naza Mmbaga (Global Ecology and Conservation, 2021)
Community awareness and participation in biodiversity conservation is vital for the establishment of community based conservation (CBC). However little information is available on the awareness and involvement of local communities adjacent to Kihansi catchment areas (KCA) on the conservation of re-introduced Kihansi spray toad (KST) and their habitat. This study focused on assessing the awareness and involvement of local communities adjacent to the KCA on the conservation of the re-introduced KSTs and their habitats. The study was conducted in three villages located adjacent to the Kihansi river gorge namely; Mgugwe, Udagaji and Ukami. Semi-structured questionnaires with both open and closed-ended questions were used to collect data from the respondents from villages surrounding the Kihansi Gorge through a cross-sectional survey. The awareness of local communities on the re-introduced KST was as follows; 98.9% (n = 361) had heard about KST and the variation across villages was significant (p < 0.05). In addition, 46.03% (n = 168) had ever seen the toads although only 27. 67% (n = 101) were able to identify the toads through their physical features. About 43.01% (n = 157) of people heard about KST through friends, while 33.15% (n = 121), and 23.84% (n = 87) heard from experts and local government leaders respectively with insignificant variation across the three villages (p = 0.236). The participation of local communities in conservation was low (<30%) which was related to little awareness of local communities on the re-introduced KST. Challenges such as habitat destruction, pollution, fires, and predation by invasive species have been reported to affect KSTs and their habitats. The study recommends strengthening the participation of local communities in habitat restoration, conservation education, and research activities on the re-introduced KST.